The living reminder : service and prayer in memory of Jesus Christ - Nouwen, Henri J. M. (New York Seabury Press, 1977)
In three chapters the author formulates and answers a new and compelling question: Who am I as a living memory of God? The challenge to Christians is to become a living reminder of God. The way to meet this challenge is to seek a life in which personal prayer and service to others sustain and enrich one another. Addressed to all Christians who want to strengthen and deepen the meaning of their lives.
Keywords: Clergy -- Religious life. Spiritualiteit. Pastoraat